Treatment of perforated colon carcinomas-outcomes of radical surgery - Daniels, Marc; Merkel, Susanne; Agaimy, Abbas; Hohenberger, Werner (International Journal of Colorectal Disease, 2015)
When patients present with a perforation of a colon cancer (CC), this situation increases the challenge to treat them properly. The question arises how to deal with these patients adequately, more restrictively or the same way as with elective cases.Between January 1995 and December 2009, 52 patients with perforated CC and 1206 nonperforated CC were documented in the Erlangen Registry of Colorectal Carcinomas (ERCRC). All these patients underwent radical resection of the primary including systematic lymph node dissection with CME. The median follow-up period was 68 months.The median age of the patients in the perforated CC group was significantly higher than in the nonperforated CC group (p = 0.010). Significantly, more patients with perforated CC were classified in ASA categories 3 and 4 (p = 0.014). Hartmann procedures were performed significantly more frequently with perforation than with the nonperforated ones (p < 0.001). If an anastomosis was performed, the leakage rate of primary anastomoses did not differ (p = 1.0). Cancer-related survival was significantly lower with perforated cancer (difference 12.8 percentage points) and by 9.6 percentage points for observed survival, if postoperative mortality was excluded.Perforated CC patients should be treated basically following the same oncologic demands, which are CME for colonic cancer including multivisceral resections, if needed. This strategy can only be performed if high-quality surgery is available, permanently.
EVALuna2:6709